Remote ECG monitoring to reduce complications following transcatheter aortic valve implantations: the Redirect TAVI study . Issue 9 (14th June 2022) - Natarajan, Madhu Kailash; Sheth, Tej Narendra; Wijeysundera, Harindra Channa; Chavarria, Jorge; Rodes-Cabau, Josep; Velianou, James Louis; Radhakrishnan, Sam; Newman, Toni; Smith, Amanda; Wong, Jorge Alfredo; Schwalm, Jon David; Duong, Monica; et al.
Abstract: Aims: The optimal strategy of monitoring for conduction disturbances in patients undergoing transcatheter aortic valve implantation (TAVI) is uncertain. We evaluated a pre- and post-TAVI remote ambulatory cardiac monitoring (rACM) strategy for identification of conduction disturbances and to reduce unplanned pre-discharge post-TAVI permanent pacemaker implantation (PPMI). Methods and results: REdireCT TAVI (NCT0381820) was a prospective cohort study of patients referred for outpatient TAVI. Patients with prior PPMI were excluded. Remote ambulatory cardiac monitoring consisted of 2 weeks of continuous electrocardiogram (ECG) monitoring (Pocket-ECG TM ) both before and after TAVI. Compliance to monitoring, frequency of notifications, unplanned PPMI post-TAVI, and length of hospitalization were measured. Between June 2018 and March 2020, in 192 undergoing TAVI (mean age: 81.8 years; female sex 46%; balloon-expandable valve 95.3%), compliance to rACM was 91.7% pre-TAVI (mean duration: 12.8 days), and 87.5% post-TAVI (mean duration: 12.9 days). There were 24 (12.5%) rACM notifications (13 pre-TAVI; 11 post-TAVI) resulting in 14 (7.3%) planned PPMI: seven pre-TAVI [due to sinus pauses n  = 2 or atrio-ventricular block (AVB) n  = 5] and seven post-TAVI [due to sinus pauses n  = 1 or AVB n  = 5 or ventricular tachycardia (VT) n  = 1]. In addition, nine (4.7%) patients received pre-TAVI PPMI due to high-risk baseline ECG (right bundle branch block with hemi-block or prolonged PR interval). Unplanned PPMI post-TAVI during index hospitalization occurred in six (3.1%) patients due to AVB and in one patient readmitted with AVB. The median length of stay post-TAVI was 1 day. Conclusion: A strategy of routine rACM was feasible and frequently led to PPMI. Our approach of 2-week rACM both pre- and post-TAVI achieves both high patient compliance and sufficient surveillance. Clinical trial registration: Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT03810820